2016
DOI: 10.1371/journal.pgen.1006496
|View full text |Cite
|
Sign up to set email alerts
|

NUCLEAR FACTOR Y, Subunit A (NF-YA) Proteins Positively Regulate Flowering and Act Through FLOWERING LOCUS T

Abstract: Photoperiod dependent flowering is one of several mechanisms used by plants to initiate the developmental transition from vegetative growth to reproductive growth. The NUCLEAR FACTOR Y (NF-Y) transcription factors are heterotrimeric complexes composed of NF-YA and histone-fold domain (HFD) containing NF-YB/NF-YC, that initiate photoperiod-dependent flowering by cooperatively interacting with CONSTANS (CO) to drive the expression of FLOWERING LOCUS T (FT). This involves NF-Y and CO binding at distal CCAAT and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 71 publications
2
58
0
Order By: Relevance
“…In accordance with many previous reports, we found that Arabidopsis plants grown at 15°C flowers significantly later than at higher ambient temperatures and in their rosette leaves the expression level of FT is lower than at higher ambient temperatures (Figure ). The expression level of FT among other factors is also regulated by another NF‐Y complex (composed of NF‐YA2, NF‐YB2, NF‐YC3; Siriwardana et al, ). The NF‐YA2 transcript is cleaved by miR169h‐n‐5p, according to our degradome analysis (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with many previous reports, we found that Arabidopsis plants grown at 15°C flowers significantly later than at higher ambient temperatures and in their rosette leaves the expression level of FT is lower than at higher ambient temperatures (Figure ). The expression level of FT among other factors is also regulated by another NF‐Y complex (composed of NF‐YA2, NF‐YB2, NF‐YC3; Siriwardana et al, ). The NF‐YA2 transcript is cleaved by miR169h‐n‐5p, according to our degradome analysis (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the list also contains a number of genes potentially related to the regulation of flowering and flowering time ( supplementary table 6 , Supplementary Material online). These genes include, for example, the one coding for the Ultraviolet-B receptor UVR8, the one encoding a Phosphorylcholine cytidylyltransferase protein and the one encoding a subunit of the Nuclear Factor Y. UV-B regulates photomorphogenesis and flowering ( Yin and Ulm 2017 ), the Nuclear Factor Y transcription factors initiates photoperiod-dependent flowering by cooperatively interacting with CONSTANS to drive the expression of FLOWERING LOCUS T (FT) ( Siriwardana et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dr1 represses RNAP II transcription by binding to TBP to prevent the formation of an active transcription complex. Members of the heterotrimeric NF-Y transcription factor family in Arabidopsis initiate photoperiod-dependent flowering and also required for activation of the FT promoter by initiating downstream events leading to floral transition ( Siriwardana etal. 2016 ).…”
Section: Discussionmentioning
confidence: 99%